Differentiating lava slip planes from tectonic faults: A key issue in structural geology - Tibaldi, A; Bonali, FL; Mariotto, FP; Russo, E (Global and Planetary Change, 2018)
The correct geological and structural survey of rock successions containing lava deposits may be biased by the possible confusion between tectonic faults and slip planes produced by lava flow sectors moving at different velocities during emplacement. Microtectonic features on slip planes resulting from lava emplacement, here named “lava slip planes” can have a very similar appearance to slickensides formed under tectonic deformation. In order to come up with criteria to distinguish between the two types of structures, slip planes of various extent from recent trachytic lava flows on Ischia Island (Italy), and basaltic lavas at Mt. Etna (Italy) and along the Northern Volcanic Zone in Iceland, have been studied in detail in the field, sampled, and analysed also with the Scanning Electrone Microscope. Strike-slip planes dominate along flow margins while reverse slip planes dominate near eruptive centers. Normal slip planes can also be found at the sides and at the front of lava flows. Slip planes form at thermal boundaries that enable plastic/brittle deformation and favour the development of shear zones. The rheological properties of the lava should be such that the material has developed a shear strength. Although the best criterion to recognize a lava slip plane is the evaluation of its confinement to a single depositional unit, this approach can be rarely used, due to the frequently limited (decimetre- to meter-sized) outcrop of slip planes. The best criterion, which can be used directly in the outcrop as well as by means of a microscope, is the individuation of burrs, which are sub-millimeter to centimeter-size portions of the slip surface that get dragged away in the direction of movement of the missing block.